Evaluation of Health Screening for Hajj Pilgrims at Hajj Dormitory in Preventing the Spread of Infectious Diseases - Widowati, Ade Triana; Astari, Lina Fitria; Milliana, Alvi (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2025)
Coronavirus disease 2019 (COVID-19) is a pneumonia caused by a new type of coronavirus, named Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The risk of spreading infectious diseases during Hajj is very high, given the mass migration of pilgrims from different countries. In the process of receiving pilgrims at the Sukolilo Hajj Dormitory in Surabaya, efforts to screen for COVID-19 and other infectious diseases are carried out by monitoring temperature using a thermal scanner. This study aims to evaluate the effectiveness of health screening of pilgrims at the Sukolilo Surabaya Hajj Dormitory in preventing the spread of infectious diseases, especially COVID-19. In addition, this study identifies factors that influence pilgrims' compliance with screening procedures as well as policy implications in improving health surveillance in the future. This study used a descriptive method with an observational approach to assess the health screening process of pilgrims arriving at the Sukolilo Hajj Dormitory in Surabaya in 2024. The research sample was selected using purposive sampling technique, involving pilgrims who had a body temperature ≥37.5°C or experienced respiratory symptoms. The results showed that most pilgrims who underwent body temperature screening and follow-up examinations complied with the established procedures. However, several factors were found to influence compliance, such as the level of understanding of the importance of screening, fear of the swab procedure, and post-travel fatigue factors. In this case, education provided by health workers is proven to increase pilgrims' compliance with the screening.